Learning the missing channel - Heigwer, Florian (Nature machine intelligence, 2022)
Microscopy-based drug screens with fluorescent markers can shed light on how drugs affect biological processes. Without adding markers and imaging channels, which is cumbersome and costly, a new generative deep-learning method extracts new fluorescence channels from images, potentially improving the drug-discovery pipeline.
Gesehen am 09.11.2022